2011
DOI: 10.1007/s11270-010-0739-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent Atmospheric Deposition and its Effects on Sandstone Cliffs in Bohemian Switzerland National Park, Czech Republic

Abstract: The protected area "Bohemian Switzerland National Park" with its characteristic sandstone landscape was influenced by the long-term air pollution and acidic deposition within the area known as Black Triangle (located where Germany, Poland, and the Czech Republic meet, is one of the Europe's most polluted areas). The local Upper Cretaceous sandstone is subhorizontally stratified, fine-to coarse-grained, quartz dominated, with low content of clay minerals. One of the significant negative effects of the intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The local hydrodynamic regime (rapid changes in rock massif saturation with percolate solutions, infiltration and accumulation areas), which is of crucial importance to the correct assessment of the intensity and distribution of salt efflorescence and the associated processes of the chemical weathering of the rock body (Zvelebil et al 2002;Vařilová et al 2011aVařilová et al , 2011b, was identified by using the non-standard method of DEMP. Commonly used methods to identify moisture distribution, like resistivity tomography profiling (ERT) (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The local hydrodynamic regime (rapid changes in rock massif saturation with percolate solutions, infiltration and accumulation areas), which is of crucial importance to the correct assessment of the intensity and distribution of salt efflorescence and the associated processes of the chemical weathering of the rock body (Zvelebil et al 2002;Vařilová et al 2011aVařilová et al , 2011b, was identified by using the non-standard method of DEMP. Commonly used methods to identify moisture distribution, like resistivity tomography profiling (ERT) (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Here the sandstone percolates sub-vertically infiltrates along several secondary inhomogeneities into the interior of the rock massif. Distribution of moisture within the PBRA is generally influenced by the existence of sub-vertical fissures and micro fissures that serve as preferential pathways of gravitational infiltration of rainfall and melting water under a gradual weakening of the surroundings (Young et al 2009;Vařilová et al 2011a).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The cement holding the rock together consists of iron oxyhydroxide and clay minerals, primarily kaolinite. Typically, the rock's surface is covered by a newly formed amorphous SiO2 crust resulting from secondary silicification [10,[21][22][23][24]. The natural processes of bedrock erosion and accumulation of sediments as a continuation of the geological development are still active in the BSNP.…”
Section: Regionmentioning
confidence: 99%
“…Frequent extreme weather brings natural disasters such as droughts and wildfires. We anchor our text in articles about the past decade's drought and fires in Czechia [14][15][16]20] and texts characterizing the BSNP and regional geology [9,10,[21][22][23][24]. Several articles described geological (geographical) fieldwork and its specifics [25,26] and teaching about climate change [27][28][29].…”
Section: Introductionmentioning
confidence: 99%